2013
DOI: 10.1007/s00216-013-7300-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination and pharmacokinetic study of the diacid metabolite of norcantharidin in beagle plasma by use of liquid chromatography–tandem mass spectrometry

Abstract: Because norcantharidin (NCTD) is unstable and subject to ring opening and hydrolysis, the diacid metabolite of norcantharidin (DM-NCTD) is the stable form of NCTD found in normal saline solution. Conversion of NCTD to DM-NCTD is almost 100%, making it possible to determine and investigate the pharmacokinetics of DM-NCTD converted from NCTD. In this paper, a sensitive, simple and selective liquid chromatographic-tandem mass spectrometric method was developed and validated for determination of DM-NCTD in beagle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…9 The pharmacokinetic study revealed that the risk of DM-NCTD intoxication may increase at high doses, and these results were consistent with the reported adverse effects for adults administered the high clinical dosage in the PRC. It is precisely because of these reasons that our study focused on increasing the t ½ and decreasing the potential adverse effects of DM-NCTD when the drug was used at a moderate dose.…”
Section: Dose Of Dm-nctdsupporting
confidence: 81%
See 2 more Smart Citations
“…9 The pharmacokinetic study revealed that the risk of DM-NCTD intoxication may increase at high doses, and these results were consistent with the reported adverse effects for adults administered the high clinical dosage in the PRC. It is precisely because of these reasons that our study focused on increasing the t ½ and decreasing the potential adverse effects of DM-NCTD when the drug was used at a moderate dose.…”
Section: Dose Of Dm-nctdsupporting
confidence: 81%
“…The apparatus and LC-MS/MS conditions were the same as those described in our previous study. 9 Whole tissues and tumor samples were collected from the mice and stored at −80°C until use. The samples were homogenized in saline (tissue or tumor:water ratio of 1:4, w/v).…”
Section: Validation Of Analytical Methods In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…NCTD was previously shown to induce cell-cycle arrest through G2 arrest. 21 , 22 However, some groups have also suggested that NCTD inhibits the cell cycle at the G1 or the S phase. 8 , 23 As we know, there were two important stages in the cell cycle, which were the G2 phase to the M phase and the G1 phase to the S phase.…”
Section: Discussionmentioning
confidence: 99%
“…Although NCTD greatly reduces the toxicity of CTD, there is still a certain degree of urinary toxicity, and organ toxicity in high-dose or long-term use [ 42 , 43 ]. Moreover, the poor solubility, short half-life, fast metabolism, as well as high venous irritation and weak tumor targeting ability limit its wide clinical application [ 44 46 ].…”
Section: Introductionmentioning
confidence: 99%